Making sense of evidence: using research training to promote organisational change. (3rd September 2019) - Wilkinson, K.; Boyd, K.; Pearson, M.; Farrimond, H.; Lang, I. A.; Fleischer, D.; Poole, A.; Ralph, N.; Rappert, B.
Abstract: Many have argued that the development of evidence-based policing (EBP) depends on those in law enforcement agencies receiving appropriate training in research methodologies and data analysis. Despite this, there are few detailed accounts of such training and its delivery. This paper describes and evaluates the contribution of training workshops for police officers and staff in driving forward EBP. The workshops, developed based on a model used in healthcare, sought to provide attendees with the knowledge, skills, and confidence to engage with research evidence during their work, and sat within a wider plan for organisational change within one force in England. We outline the development and delivery of the workshops, which were undertaken using an action research approach, and assess their impact including subsequent changes to practice. Finally, we consider the role these workshops played within organisational change, and reflect on how EBP can be promoted within academic-police collaborations.